Dimensions of Effective Teaching - Pillai, K. P. P. (Journal of Engineering Education Transformations, 1994)
At the outset it may be stated that effective teach in g is not solely dependent on teachers. Students also have responsibilities to learn. While the student's responsibilities are individual and personal, the teachers' responsibilities are collective and professional. The present discussion is subject to this proviso.